Desempenhos emergentes e leitura funcional em crianças com transtornos do espectro autístico - Gomes, Camila Graciella Santos (2007)
People with autism display a number of marked deficits in communication, symbolic or imaginative activities, reciprocal social interaction and the presence of a pattern of restrict behavior. Follow-up studies indicate that people with autism show difficulties in learning relationships between stimulus through conventional interventions. The first study assessed the performance of twenty persons with autism in an identity matching-to-sample task, using two procedures with different stimuli arrangements and different response requirements. The typical matching procedure presented one sample and three comparison stimuli; the adapted matching displayed three samples and three comparison stimuli simultaneously. The average scores of correct performance were significantly higher under the adapted matching than under the typical matching, but the inter-individual variability was large and the adapted arrangement favored mainly the performance of participants with lower scores. The second study investigated the emergence of performance that had not been directly taught to autistic children. Four children with autism learned to match one-element comparison stimuli to twoelement sample stimuli, in adapted matching-to-sample tasks. They also learned to name pictures. It was used a multiple baseline design. Relations between pictures and printed words and identification/nomination of printed words had been tested and the outcomes indicate the emergence of performances that had not been directly taught and the formation of stimulus equivalence classes. The dataset suggests the importance of the organization of stimuli in the tasks and the teaching of arbitrary relations as part of the conditions to promote the establishment of symbolic behavior in people with autism